Enabling environment for Sustainable Intensification of Mixed Farming System for gender transformative change in mid-hills of Nepal: What to consider? - Koirala, Sanju; Buchy, Marlène; Khadka, Manohara; Shakya, Shristi; Neupane, Nihari (International Water Management Institute, 2023)
Nepal’s agriculture sector is facing various challenges including, amongst others, inadequate infrastructures, investment, labor shortage, climate-induced changes, and weak agriculture governance mechanisms. With the increase in migration trends among males, the ‘left behinds’ in the mid-hills of Nepal, are mostly women, middle-aged men, and the elderly. Due to the massive decline in the labor force, arable land is left fallow, ultimately affecting food security. Within this context, IWMI and CIMMYT are conducting action research in Khotang and Surkhet districts located in the mid-hills of Nepal as part of a CGIAR initiative on the Sustainable Intensification of Mixed Farming System (SI-MFS). The intention is to suggest sustainable, gendertransformative pathways to address some of the challenges by deploying locally viable sociotechnical innovations selected, profiled, and piloted in consultation with different stakeholders. The successful implementation and scaling of innovation depends on softer elements such as policies and regulations, informal institutions–power relations, value chains, markets, financial mechanisms, and infrastructure. Considering this, the study aims to assess factors that support and/or constrain the SI-MFS in Nepal to bring about transformative changes in the lives of women, the elderly and marginalized farmers. Using a gendertransformative approach (GTA) as a framework, we are trying to understand how GTA matches with the goals set by SI-MFS initiatives. This study takes a reflective approach and critically assesses SI-MFS activities planned and implemented in Nepal. At the initial stage of the research, we will be sharing reflections on challenges we faced in contextualizing SI-MFS activities in Nepal within GTA.